MASS MEDIA’S ETHICAL IMPACT ON CHILDREN - Nuredin, Mensur; Nesimi, Abdulxhemil (International Scientific Journal Vision, 2021)
The phenomenon of media since its emergence has been influential on people and the society. The size of this effect has changed in direct proportion to the accessibility level of the media. While the media activities which took place only in written form in the first periods were effective on very few people, the formation of audio and visual media structures over time had expanded the influence of the media. Today, the media has gained the feature of being effective on large masses, thanks to the ease of access, interaction feature and the conveniences provided in these areas of the social media structures created in the virtual environment. The social media structure plays a decisive role on the individual and then on the social structure. Although this determination is sometimes unconsciously, in general it is an undeniable fact that the media has a directing effect on society. When it comes to the effects of communication tools, one of the most discussed issues is the effect of media content on children. It is accepted that since the child has not reached full maturity both physically and mentally, he is more open to influences and needs special protection from the effects that may harm his development. In the context of the media, the protection of children shows a dual structure: protecting children from the exposure to content that may harm their development and protecting children who are the subject of the media content. While providing the aforementioned protections is tried to be realized by laws, on the other hand, solutions are sought with ethical rules to the problems that arise.